2021
DOI: 10.11648/j.ijmpem.20210601.12
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Bitumen Properties Using Waste Polymer in Context of Bangladesh

Abstract: Proper disposal of plastics and its derivatives is one of the biggest challenges all over the globe. Due to the improper management of plastic product environment is being polluted. Plastic waste generation and plastic waste-based pollution in Bangladesh is leaping at a high pace. Among numerous ways of disposal of waste plastics, one can be using it in flexible pavement construction. According to the Bangladesh Waste Database 2014, Dhaka city alone produces 25.44% (5,925.51 tons/ day) of waste, of which 8.45%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…An Increase in stiffness makes bitumen less flexible, which causes a reduction in ductility. 28 Reduction in ductility could be because of the interlocking of PEG molecules with bitumen. 29 Figure 5 shows the decrease in ductility from 143 cm to 83 cm as percentage of PEG increases from 2% to 8% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…An Increase in stiffness makes bitumen less flexible, which causes a reduction in ductility. 28 Reduction in ductility could be because of the interlocking of PEG molecules with bitumen. 29 Figure 5 shows the decrease in ductility from 143 cm to 83 cm as percentage of PEG increases from 2% to 8% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A research study investigated the effect of two different clays on EVA-modified bitumen and found that nano-clay improved the thermo-mechanical properties as well as provided better homogeneity, performance, and stability [321]. In addition to that, polymer dispersion improved with the addition of nanoclay [322] depending upon the concentration and functionality of PE [323].…”
Section: Nano-clay and Nanomaterialsmentioning
confidence: 99%